Kharif Potato Production in India overcoming the lapses in its marketing - Rana, Rajesh K; Kumar, Sanjay; Chaudhary, K R (Indian Farming, 2016)
The potato farmers in the states of Himachal Pradesh and Uttarakhand sell their potatoes in markets of NCR and nearby areas under the popular brand name pahari aloo. However, malpractices and misbranding of pahari aloo in the target markets are leaving lower potato profits compared to the alternative off season vegetables grown by these hilly farmers. In addition the brand pahari aloo has not been properly defended and exploited by unorganized small and marginal potato farmers of these two states. As a result farmers of these two states are progressively losing their interest in potato crop. However, right marketing strategy for this specialty product is not only likely to generate superior profits for the small sized hill potato farmers, but this will tremendously enhance consumption experience and satisfaction level of high end targeted potato consumers.